2016
DOI: 10.1590/1518-8345.0549.2809
|View full text |Cite
|
Sign up to set email alerts
|

Stages of change of behavior in women on a multi-professional program for treatment of obesity

Abstract: Objective: to ascertain the effectiveness of an intervention program in relation to anthropometric measurements and stage of readiness for behavioral change in women with excess weight. Methods: the intervention group (IG) was made up of 13 women, and the control group (CG), by 20. The intervention lasted 16 weeks, and included the practice of guided physical activity three times a week, and health education once a week. The application of the questionnaire on stage of readiness for behavioral change, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
0
5
1
12
Order By: Relevance
“…While 62 participants attended all meetings, 9 of them missed one session. The adherence rate reported in this study was higher than that reported in other education intervention studies [22][23][24][25]. The higher adherence rate may be related to the fact that a higher ratio of participants in this group considered themselves overweight and were more careful in avoiding high cholesterol.…”
Section: Discussioncontrasting
confidence: 81%
“…While 62 participants attended all meetings, 9 of them missed one session. The adherence rate reported in this study was higher than that reported in other education intervention studies [22][23][24][25]. The higher adherence rate may be related to the fact that a higher ratio of participants in this group considered themselves overweight and were more careful in avoiding high cholesterol.…”
Section: Discussioncontrasting
confidence: 81%
“…This can be explained by the fact that we have directed efforts to PA and not to other behaviors that could also contribute to weight loss. For example, a study that applied an intervention that included PA along with nutritional guidelines had a statistically significant reduction of BMI 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study is a part of research concerning the efficacy of obesity treatment, in which not only weight loss, but also behavioral changes are considered intervention endpoints [19]. The behavioral dimension of obesity treatment is vital as the inclusion of new eating behaviors in the daily routine is a prerequisite for the efficacy of obesity treatment and maintenance of its effects [19][20][21]. The major goal of the study was to determine whether dietary management of simple obesity resulted in lasting behavioral changes in eating patterns (behaviors) and affected level of nutrition knowledge.…”
Section: Discussionmentioning
confidence: 99%